2020
DOI: 10.1111/mcn.12948
|View full text |Cite
|
Sign up to set email alerts
|

The effect of a combined intervention on exclusive breastfeeding in primiparas: A randomised controlled trial

Abstract: An antenatal/postnatal intervention involving proactive telephone support and written materials was conducted among primiparas. Four hundred women, from the Split‐Dalmatia County, Croatia, were randomized between November 2013 and December 2016 into three groups: intervention (IG), active control (ACG) and standard care (SCG). Primary outcome was exclusive breastfeeding (EBF) at 3 months. Secondary outcomes included breastfeeding difficulties, attitudes towards infant feeding, breastfeeding self‐efficacy and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 14 publications
0
19
0
1
Order By: Relevance
“…A total of nine studies [ 4 , 5 , 7 , 8 , 11 , 12 , 14 , 17 , 19 ] reported exclusive breastfeeding rates at 3 months after delivery. The results of random effect model analysis showed that mHealth-based interventions significantly improved the rate (OR 3.05, 95% CI 1.97-4.73; P <.001; I 2 =70%).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…A total of nine studies [ 4 , 5 , 7 , 8 , 11 , 12 , 14 , 17 , 19 ] reported exclusive breastfeeding rates at 3 months after delivery. The results of random effect model analysis showed that mHealth-based interventions significantly improved the rate (OR 3.05, 95% CI 1.97-4.73; P <.001; I 2 =70%).…”
Section: Resultsmentioning
confidence: 99%
“…A total of three [ 5 , 6 , 15 ] studies reported on breastfeeding efficacy. The results of random effects model analysis showed that mHealth-based interventions significantly improved breastfeeding efficacy compared with usual care (MD 8.15, 95% CI 3.79-12.51; P <.001; I 2 =88%).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations